PERAN STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DAN KOMUNIKASI ORGANISASI DALAM MENINGKATKAN KINERJA BISNIS - Ni Kadek Suryani (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2023)
Human resource management and organizational communication strategies greatly influence organizational performance. This study aims to explore the extent to which human resource strategies and organizational communication can improve organizational performance. The research approach used is a qualitative descriptive approach with literature study as a collection technique from previous research articles and books that are relevant and up to date. The research results illustrate that there is a link between human resource management strategy and organizational communication which significantly influences organizational performance which cannot be ignored. Implementing effective human resource strategies and organizational communication will improve organizational performance so that the organization can be more competitive in the market. Human resources strategy and organizational communication are very crucial tools to ensure the survival and operations of the organization in the future.